Peran Non Performing Financing terhadap Profitabilitas Bank Pembiayaan Rakyat Syariah dengan Inflasi sebagai Variabel Moderasi - Muhammad - Zulkarnain; Heliyani Heliyani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
The research aims to examine the role of Non-Performing Financing (NPF) on the profitability of financing in Sharia Banks with inflation as a moderation variable. The population of this research is Islamic Rural Banks in West Sumatra Indonesia, which was registered in the Financial Services Authority (OJK) in the 2015-2018 period. Samples of research were taken purposively as many as seven units of Islamic Rural Banks which were spread in West Sumatra Indonesia. The data analysis technique used is a regression method with panel data (pooled data) which is a combination of cross section and time series data using Software Eviews8. The results of the analysis showed that Non-Performing Financing (NPF) has a negative effect on profitability, which is proxied by ROA. Furthermore, this research proves that the inflation does not moderate or weaken the influence of the NPF on the profitability of Islamic Rural Banks. This research contributes in expanding the direct relationship between NPF and profitability which in previous research was not elaborated further.